The Giunta/Junta Printers (15th and 17th century), in Peralada’s Palace Library - Padrosa Gorgot, Inés (Revista General de Información y Documentación, 2022)
Today’s target is analize a set of about forty printed books belonging to sixteenth and seventeenth century with a common point: having been printed by the prestigious italian lineage which appears by such different forms as Giunta, Giuntae, Giunctam, Giunti, Iuntae o Junta, depending on the country where they worked: Italy, France or Spain. About fifty per cent of them comes from Rocaberti’s library, the others thanks to D. Miquel Mateu Pla (1898-1972). With the idea of giving the researcher the following chapter of the library’s story, we’ll devote the introduction part to Miguel Mateu and its cultural and bibliophile trajectory. Next, we’ll proceed to enumerate the items kept in Peralada printed in three different countries and the cities where Giunta family operated –in Italy (Venice and Florence); in France (Lugduni) and in Spain (Burgos, Salamanca and Madrid)– and analyze its special and unique characteristics as bookbindings, Desamortizacion origins, previous owners and different sort of exlibris.